Preventing Uranium(VI) redissolution in water after treatment with zerovalent iron nanoparticles by passivation with chromium(VI) - Crespi, Julieta; Fabris, Guido Berdina; Halac, Emilia Beatriz; Leyva de Guglielmino, Ana Gabriela; Zampieri, Guillermo Enrique; Quici, Natalia (Italian Association of Chemical Engineering, 2021)
Fil: Crespi, Julieta. Comisión Nacional de Energía Atómica. Gerencia del Área de Seguridad Nuclear y Ambiente. Gerencia de Química (CAC); Argentina. Universidad Nacional de San Martín. Instituto Sabato; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina